Differential Dopamine D1 and D3 Receptor Modulation and Expression in the Spinal Cord of Two Mouse Models of Restless Legs Syndrome - Meneely, Samantha; Dinkins, Mai-Lynne; Kassai, Miki; Lyu, Shangru; Liu, Yuning; Lin, Chien-Te; Brewer, Kori; Li, Yuqing; Clemens, Stefan (Frontiers in Behavioral Neuroscience, 2018)
Restless Legs Syndrome (RLS) is often and successfully treated with dopamine receptor agonists that target the inhibitory D3 receptor subtype, however there is no clinical evidence of a D3 receptor dysfunction in RLS patients. In contrast, genome-wide association studies in RLS patients have established that a mutation of the MEIS1 gene is associated with an increased risk in developing RLS, but the effect of MEIS1 dysfunction on sensorimotor function remain unknown. Mouse models for a dysfunctional D3 receptor (D3KO) and Meis1 (Meis1KO) were developed independently, and each animal expresses some features associated with RLS in the clinic, but they have not been compared in their responsiveness to treatment options used in the clinic. We here confirm that D3KO and Meis1KO animals show increased locomotor activities, but that only D3KO show an increased sensory excitability to thermal stimuli. Next we compared the effects of dopaminergics and opioids in both animal models, and we assessed D1 and D3 dopamine receptor expression in the spinal cord, the gateway for sensorimotor processing. We found that Meis1KO share most of the tested behavioral properties with their wild type (WT) controls, including the modulation of the thermal pain withdrawal reflex by morphine, L-DOPA and D3 receptor (D3R) agonists and antagonists. However, Meis1KO and D3KO were behaviorally more similar to each other than to WT when tested with D1 receptor (D1R) agonists and antagonists. Subsequent Western blot analyses of D1R and D3R protein expression in the spinal cord revealed a significant increase in D1R but not D3R expression in Meis1KO and D3KO over WT controls. As the D3R is mostly present in the dorsal spinal cord where it has been shown to modulate sensory pathways, while activation of the D1Rs can activate motoneurons in the ventral spinal cord, we speculate that D3KO and Meis1KO represent two complementary animal models for RLS, in which the mechanisms of sensory (D3R-mediated) and motor (D1R-mediated) dysfunctions can be differentially explored.